The Temperature Measuring Helmet Based Aduino Promini with MLX90614-DCI Sensor: Helm Pengukur Suhu Badan Berbasis Arduino Promini dengan Sensor MLX90614-DCI - Siddiq, Wahyu Ja'far; Sulistiyowati, Indah (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2021)
The Covid-19 pandemic that is currently spreading in Indonesia has claimed thousands of lives. Coronavirus Disease is characterized by the main clinical symptoms of fever gretar than 38 Degree C, coughing, to shortness of breath. In preventing its spread, the government conducts early detection by examining the main symptoms in the form of a fever and enforcing health protocols on each line. Therefore, we need an appropriate innovation that can make it easier for officers/guards to check human body temperature, especially in crowded places such as at airports, malls, or on the highway. Currently, body temperature measurement equipment is widely used, which allegedly made many errors in detecting it. Therefore, an innovative helmet was created that can be used by guards, security and even the police to detect body temperature based on the Arduino Pro Mini with the MLX90614-DCI sensor and the output is the real body temperature displayed on the LED screen. When the body temperature reads more than 38 Degree C, the helmet will turn on a buzzer and an LED to show that the target measurement is in a fever condition, and it is recommended going to the health center for further examination. This tool has been tested, and the sensor readings have an accuracy at a distance of 100 cm with several participants and the sensor readings are compared with the reading values from the alpha one thermometer and the measurement results have an accuracy level of 95 percent. Keywords Arduino Promini, Covid19, MLX90614-DCI, Infrared Thermometer.